The workplace : - Pace, Joe (Joseph) (McGraw-Hill, 2006)
Developed by Dr. Joe Pace and incorporating the same material he has used to guide thousands of students and to train hundreds of instructors across North America, The Professional Development Series is designed to teach the personal skills that lead to college, job, and career success.